A Case Study on Behavior of Performing Art Appreciators in Public Space: Indonesian Puppet (Wayang) Performance Arts and Video Mapping - Andri Pahrulroji; Zakarias Sukarya Soeteja (Universitas Pendidikan Indonesia (UPI), 2022)
The presence of video mapping performances in Indonesia influences the behavior of appreciators in public spaces through acculturation. The propagation of Islamic teachings through wayang (puppet) shows had a fascinating impact on the history of public performances in Indonesia. Cultural acculturation can affect the behavior of public space appreciators or vice versa. This situation depends on the adaptability of appreciators with an Indonesian cultural background to changes in the format of public space performances. This change pertains to performance art incorporating innovative technology, such as wayang performances and video mapping. In order to conduct research on changes in appreciator behavior in public spaces, a descriptive-analytic method with an ethnographic and ethnological approach was required to examine Indonesian appreciators' ethnicity through wayang performances and literature studies. Then, it was compared to how the observatory video mapping performance was analyzed, such as Carl Gustav Jung's theory or Pierre Bourdieu's habitus perception, where the memory of previous inherited behavior influences current behavior or individual behavior is influenced by its social experience. This study's analysis revealed that the behavior of appreciators in public spaces, such as video mapping performances in Indonesia, which are renewable with the use of technology, is nearly similar to that of wayang performance appreciators.